2001
DOI: 10.1071/ah010085
|View full text |Cite
|
Sign up to set email alerts
|

Community-based continuity of midwifery care versus standard hospital care: a cost analysis

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 8 publications
0
45
0
Order By: Relevance
“…The STOMP model was established within the existing budget of a metropolitan teaching hospital and evaluated in a randomised controlled trial. The clinical outcomes, antenatal experiences of women and costs are reported elsewhere (Homer et al 2000;Homer et al 2001b;Homer et al 2001a). An important outcome measure in the trial was the experience of women as measured in the postnatal period.…”
Section: Introductionmentioning
confidence: 99%
“…The STOMP model was established within the existing budget of a metropolitan teaching hospital and evaluated in a randomised controlled trial. The clinical outcomes, antenatal experiences of women and costs are reported elsewhere (Homer et al 2000;Homer et al 2001b;Homer et al 2001a). An important outcome measure in the trial was the experience of women as measured in the postnatal period.…”
Section: Introductionmentioning
confidence: 99%
“…This study endeavours to provide an economic evaluation at a local level and is consistent with previous Australian (Byrne et al, 2000;Homer et al, 2001;Tracy and Hartz, 2006), UK (Young et al, 1997) and USA (Stone and Walker, 1995) continuity of midwifery cost analyses. …”
Section: Discussionmentioning
confidence: 92%
“…In Australia, team midwifery incorporating antenatal care in a community setting (Homer et al, 2001) and Midwifery Group Practice in a stand-alone unit have been found to be cost effective (Tracy and Hartz, 2006). A comparison of birth centre care alongside a tertiary level conventional delivery suite found no difference in costs (Byrne et al, 2000).…”
Section: Introductionmentioning
confidence: 98%
“…Another Australian study comparing care by a midwife team versus routine care for both low-and high-risk women revealed that team care resulted in a cost reduction of 4.5% (Rowley et al, 1995). A third article from Australia presenting a cost analysis comparing community-based continuity of midwifery care versus standard hospital care, found that the mean costs were lower for the community-based continuity of midwifery care even after adjusting for caesarean sections (Homer et al, 2001). Even though these trials are conducted in the same country a comparison is difficult due to varied organisation of birth care and different structure of the trials (Rowley et al, 1995;Byrne et al, 2000;Homer et al, 2001).…”
Section: Introductionmentioning
confidence: 94%
“…A third article from Australia presenting a cost analysis comparing community-based continuity of midwifery care versus standard hospital care, found that the mean costs were lower for the community-based continuity of midwifery care even after adjusting for caesarean sections (Homer et al, 2001). Even though these trials are conducted in the same country a comparison is difficult due to varied organisation of birth care and different structure of the trials (Rowley et al, 1995;Byrne et al, 2000;Homer et al, 2001). A study from the USA showed that there were no differences in costs when comparing a freestanding birth centre to "traditional care" in a central New York community, but a sensitivity analysis demonstrated that freestanding birth centres could be cost effective if they increased their volume (Stone et al, 2000).…”
Section: Introductionmentioning
confidence: 97%